Oscillatory onset of rotating thermal convection subject to spatially varying magnetic fields and stable stratification - Sreenivasan, Sethulakshmy Edathara; Sahoo, Swarandeep (Physics of fluids (1994), 2024)
Convective fluid motions in deep planetary cores induce spatially and temporally varying magnetic fields observable as secular variation. Oscillatory instabilities occurring as onset modes in rapidly rotating thermal convection influenced by heterogeneous magnetic fields and stratification, investigated in this study, can be potentially linked to such observations. A plane layer approximation to near-polar and near-equatorial regions of the Earth's outer core is considered. In addition to penetrative convection and flow suppression effects, the simultaneous interaction of convective instabilities with asymmetrical magnetic fields and stable stratification is the focus of this study. The fundamental modes of magnetoconvection onset are preserved even under stable stratification, although the convection threshold is lowered irrespective of the parameter regime. The axial invariance of rapidly rotating columnar convection loses its midplane symmetry with intense localization of kinetic energy in the unstably stratified regions. The parameter regimes supporting the onset of the magnetically modified viscous oscillatory (mVO) modes are further extended toward Earthlike conditions such as high thermal conductivity (low Prandlt number, Pr) and magnetic dissipation (low Roberts number, q). Moreover, compared to fully unstable stratification, partial stable stratification enhances the range of imposed magnetic field length scale ( δ) over which the onset of mVO modes is favored. The critical field length scale ( δ⋆), above which the onset regime of the mVO modes is bounded by a minimum q, is determined. Irrespective of the rotation rate, below δ=δ⋆, the onset of the mVO mode is supported for asymptotically small q for Pr values close to the Earth's outer core.